Design and development of UAV for robotx challenge - Yong, Xun Hao (Nanyang Technological University, 2022)
The objective of this project is to develop the system used for an Unmanned Aerial Vehicle (UAV). This UAV is a vessel that will take part in the RobotX Challenge, which is an internal marine time competition involving different universities from all over the world. This report details the development process of the UAV, which includes selection of the UAV type and frame, integration of different systems of the UAV. The author is one of the team members working on this challenge, together with seven other members to build and modify an unmanned surface vehicle and an unmanned aerial vehicle. The author’s responsibilities is to build and develop the UAV system, which includes the mechanical and software side of the UAV